A comparative study of Toxoplasma gondii seroprevalence in mink using a modified agglutination test, a Western blot, and enzyme-linked immunosorbent assays. (September 2015) - Gu, Yi; Wang, Zedong; Cai, Yufeng; Li, Xiaoxing; Wei, Feng; Shang, Limin; Li, Jiping; Liu, Quan
Toxoplasma gondii can infect almost all warm-blooded animals, and many serological methods have been developed to detect T. gondii infection in a variety of animal species. In the present study, the seroprevalence of T. gondii infection in farmed mink in northeast China was determined using the modified agglutination test (MAT), a Western blot (WB), and 3 enzyme-linked immunosorbent assays (ELISAs) with protein A/G conjugate, using either of 2 recombinant dense granule antigens, GRA1 and GRA7, or Toxoplasma soluble antigens (TSA). There was no significant difference between the detection results of the GRA1-, GRA7-, and TSA-ELISAs and WB (McNemar chi-square, P > 0.05), but a significant difference was observed between MAT and WB ( P < 0.05). A near perfect agreement (97.0%) was found between the GRA7-ELISA and WB (κ = 0.83), and a substantial agreement (92.4–93.1%) was observed in the TSA- and GRA1-ELISAs (κ = 0.68–0.73). The GRA7-ELISA showed the highest sensitivity and specificity, and the lowest false-positive and negative rates, while the MAT gave both a low sensitivity and frequent false positives in comparison to the WB. Receiver operating characteristic analysis revealed the largest area under curve of 0.85 (95% confidence interval: 0.74–0.96), and the highest relative sensitivity (72.7%) and specificity (99.0%) for a cutoff value of 0.19 in the GRA7-ELISA. These results indicate that the GRA7-ELISA is suitable for detection of T. gondii infection in mink and that MAT should be used with caution.